2017
DOI: 10.1007/s10340-017-0899-z
|View full text |Cite
|
Sign up to set email alerts
|

Biological parameters of the invasive brown marmorated stink bug, Halyomorpha halys, in southern Europe

Abstract: The brown marmorated stink bug, Halyomorpha halys, is an invasive pest species, first detected in Italy in 2012. Only 2 years after this first detection, increasing damage was reported in fruit orchards in the Emilia Romagna region, the first invaded area, which is one of the most important regions for the Italian and European fruit production. In the present study, life table parameters of H. halys populations were investigated in Italy under typical temperate/Mediterranean climate conditions representative o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 34 publications
4
70
1
Order By: Relevance
“…Considering overall parasitism and predation and the high net reproductive of H. halys in the Emilia‐Romagna region (Costi, Haye, & Maistrello, ), our results suggest a low impact of the native natural enemies community in reducing populations of this invasive species in Northern Italy. This gap could be filled by introducing Trissolcus japonicus (Ashmead) (syn.…”
Section: Discussionmentioning
confidence: 63%
“…Considering overall parasitism and predation and the high net reproductive of H. halys in the Emilia‐Romagna region (Costi, Haye, & Maistrello, ), our results suggest a low impact of the native natural enemies community in reducing populations of this invasive species in Northern Italy. This gap could be filled by introducing Trissolcus japonicus (Ashmead) (syn.…”
Section: Discussionmentioning
confidence: 63%
“…At temperatures below the lower thresholds, the reduced enzyme activity results in slower or negligibly low metabolic processes, which require substantial energy to repair injuries in insects, resulting in longer developmental times [69,70]. The high temperature thresholds of 36.5 and 35.76 • C were previously reported for the Swiss [44] and US (Pennsylvania; [47]) populations of H. halys. These estimates are based on models fit to the pest's phenology data but do not support H. halys egg-to-adult development below 17 • C or above 33 • C. In contrast, we provide empirical evidence at constant temperatures where a MN population of H. halys exhibited lower and upper developmental thresholds of 17 and 36 • C, respectively.…”
Section: Discussionmentioning
confidence: 78%
“…Eggs are laid in masses of 28 (median number), predominantly on the underside of leaves. Laboratory studies in the United States found an average of 9.3 egg masses in a lifetime (113), whereas European field studies estimated fecundity to range from 2 to 15 egg masses per female, with higher oviposition rates within the overwintered adult generation (33,48). During oviposition, females transfer symbionts to the egg chorion surface.…”
Section: Life Historymentioning
confidence: 99%